Legal Protection for Minority Shareholders in Joint Venture Cooperation in Public Companies According to Indonesian Positive Law - Krisdian Rizki Havana Ndraha; Martono Anggusti; Sovia Febrina Tamaulina Simamora (PT FORMOSA CENDEKIA GLOBAL, 2025)
This writing aims to explore the Legal Protection of Minority Shareholders. Legal Protection for Minority Shareholders in Joint Venture Cooperation in Public Companies According to Positive Law in Indonesia. The research method that the author uses is the normative legal research method normative research method that focuses on understanding the laws and regulations, legal norms and also legal issues related to this writing. The method This method of writing also uses a conceptual approach, namely collecting all sources and primary legal materials and primary legal materials, where the source of this writing comes from books, legal norms and also legal issues related to this writing. Based on the results of this writing, the author obtained the fact that the regulations governing Joint Venture cooperation in Indonesia are still not clearly or explicitly regulated, especially in the protection of the parties. especially in the protection of the parties involved in the joint venture cooperation. the joint venture cooperation including minority shareholders. With the adangan of the Civil Code Civil Code, Law No. 40 of 2007 Concerning Limited Liability Companies and Law Number 25 Year 2007 on Capital Investment can certainly be utilized by the parties involved in joint venture cooperation. utilized by the pharties involved in joint venture cooperation in order to have a strong legal position before entering into a joint venture agreement. before entering into a joint venture agreement